The effect of prenatal ultrasound heating throughout gestation on rabbit fetal weight - Ahmad Zaiki, Farah Wahida; Md Dom, Sulaiman (Science and Engineering Research Support Society, 2014)
The aim of this in vivo experimental study is to determine the association between ultrasound exposure time and rabbit fetal weight. A total of 14 pregnant does were exposed to ultrasound heating for 30, 60, and 90 minutes of ultrasound exposure at their middle of each gestational stage, while another 4 pregnant does served as control. Total of 136 fetuses (1st stage, n=34 (25%); 2nd stage, n=28 (20.6%); 3rd stage, n=74 (54.4%)) were analyzed for fetal body weight. There were significant differences in fetal weight at all stages (p<0.05; 95% CI do not cross 0) of all groups at different length of exposure time. There were also negative correlation between groups with different exposure durations and fetal weight in the 1st and the 3rd stage (p<0.05; r = -0.40, p<0.05; r = -0.23 respectively). Exposure time was found poorly associated with fetal weight in the 1st and the 3rd stage (p<0.05; r2 = 0.15 and 0.04 respectively). This study suggests the heating effect of ultrasound exposure might act as a noxious agent that promotes intrauterine growth restriction in developing fetus that might consequently impacts the rabbit fetal weight. Therefore a considerably increase in awareness of negligible effects aroused from prenatal ultrasound exposure was concerned as it was widely applied to pregnant women.